Practice and Awareness Regarding Tobacco Consumption among Residents of the Hilly area of Eastern Region of Nepal - Shah, Ram Bilakshan; Subedi, Laxmi; Jha, Nilambar (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Tobacco use is a global socio-economic hazard and medical malady. The incidence of tobacco is persisting and spreading in all walks of our modern society. Methods: The cross-sectional study was conducted among residents of Dhankuta Municipality where 205 households were taken as subjects. Pretested semi-structured questionnaire was administered to the study subjects and face to face interview was conducted. Chi-square test was applied to find out the association between pattern of tobacco use and awareness of tobacco use among residents of Dhankuta municipality. Results: The awareness towards tobacco use among residents of Dhankuta municipality was found to be 41 %. The awareness of tobacco consumption was significantly higher among the female (49 %) in gender and those whose education were School Leaving Certificate (SLC) and above (44.6 %) (P<0.05). The respondents consuming tobacco have forty times lesser chances of having aware as respondents not consuming tobacco (OR=0.025). The respondents consuming tobacco for more than 20 years (12.1 %) and more than 20 sticks per day (20 %) were more aware of tobacco consumption but the difference was not significant. Conclusions: The awareness towards tobacco use among residents of Dhankuta municipality was found to be less. Male in gender, lack of education and poor occupation like famer, housewife was found to be less aware of tobacco consumption.